Recent updates on production and reproduction traits of buffalo (Bubalus bubalis): A review - Asit Jain; Akansha Singh; Tripti Jain; Sita Prasad Tiwari; Mohan Singh Thakur; Vaishali Khare; Shrikant Joshi; Satyendra Singh Tomar; Farheen Ansari (The Indian Veterinary Journal, 2024)
In many South Asian and Mediterranean countries, buffaloes are an important livestock resource, contributing milk, meat, skins, and draft power for agricultural operations, which are essential for the overall development of society. Various recent high-throughput technologies, such as molecular markers, genomic selection (GS) and genome-wide association studies (GWASs), provide an extensive range of whole-genome data and high coverage of genomic, transcriptomic and proteomic data. This review highlights these high-throughput technologies linked to the production and reproduction traits of buffaloes. The availability of recent high-quality reference genome and genotyping marker panels for buffaloes have supported many genome-based studies and provided valuable information for understanding the genetic basis of growth, functional traits, and performance traits. In conclusion, high-throughput technologies provide an opportunity to detect important markers and genomic regions associated with performance traits and also present the possibility of genomic selection as a promising strategy in buffalo breeding programs to accelerate genetic gain.